Analysis Of Raw Material Inventory Management In OTR Laundry By Applying The Economic Order Quantity (EOQ) Method - Camelia Rizki Agrina; Sari, Ernita (International Journal of Management and Business Economics, 2024)
This study aims to determine and analyze the control of the main raw material inventory at OTR Laundry with an inventory management policy using the Economic Order Quantity (EOQ) method. The study focuses on inventory management at OTR Laundry located at Jalan Ciseke, Jatinangor, Sumedang. This study uses a quantitative approach. Primary data in this study were obtained through in-depth interviews with the owner of OTR Laundry and direct observation in the field. Secondary data were obtained from inventory records and the company's financial reports. Data collection techniques used were interviews, observations, and documentation. Data analysis was carried out by calculating optimal inventory requirements using the EOQ method and comparing them with the inventory policy implemented by OTR Laundry. The calculation results show a comparison between the total cost of fragrance inventory calculated based on the OTR Laundry policy and the EOQ calculation method. Savings using the EOQ method compared to the OTR Laundry policy on inventory cost expenditure amounted to Rp313,764. The results of this study are expected to provide recommendations for OTR Laundry in increasing the efficiency of managing the main raw material inventory and reducing operational costs.